Genetic pathways in colorectal cancer. - Ilyas, M; Tomlinson, I (1996)
The model of colorectal tumorigenesis put forward by Fearon and Vogelstein has had great influence on molecular oncology. They proposed that a series of mutations occur in the progression from normal cells to colorectal cancer and that these mutations are associated with the histological features of such tumours. Several postulates of the model appear to be correct, particularly its emphasis on the stepwise accumulation of genetic changes and the inclusion of mutations at the adenomatous polyposis coli (APC) and TP53 loci. Since the publication of the original model, however, mutations at other loci have been identified which may be alternatives or additions. There is also evidence to suggest that some colorectal cancers develop along a different genetic pathway. In this review, we discuss how tumour development can occur as Darwinian evolution through selection of advantageous somatic mutations. The non-random nature of mutation selection gives rise to genetic pathways of tumorigenesis. In addition, we consider the Fearon and Vogelstein model, its shortcomings and possible additions to it. The evidence suggests that not all colorectal cancers follow the same genetic pathway during carcinogenesis.